Blackwork - Ferris, Monica (Ferris, Monica. Needlecraft mystery, 2009)
In the town of Excelsior, Minnesota, it's Halloween, and Betsy Devonshire, owner of the Crewel World needlework shop and part-time sleuth, is haunted by murder as she investigates the mysterious death of Wicca practitioner and microbrewery owner Leona Cunningham.